Self-balancing of the clamping-capacitor-voltages in the multilevel capacitor-clamping-inverter under sub-harmonic PWM modulation. - Xiaoming Yuang (IEEE Transactions on power electronics)
The paper explores the spontaneous coupled clamping-capacitor-current control loops and the resultant self-balancing property of the clamping-capacitor-voltages in the multilevel capacitor-clamping-inverter. The case of the three-level capacitor-clamping-inverter under sub-harmonic PWM modulation is dealt with first. The case of the multilevel capacitor-clamping-inverter (M>3) under sub-harmonic PWM modulation is then analyzed. Test results on a half-bridge three-level capacitor-clamping-inverter prototype under sub-harmonic PWM modulation are demonstrated